The replication fork trap and termination of chromosome replication. - Duggin, I; Wake, R; Bell, S; Hill, T (2008)
Bacteria that have a circular chromosome with a bidirectional DNA replication origin are thought to utilize a 'replication fork trap' to control termination of replication. The fork trap is an arrangement of replication pause sites that ensures that the two replication forks fuse within the terminus region of the chromosome, approximately opposite the origin on the circular map. However, the biological significance of the replication fork trap has been mysterious, as its inactivation has no obvious consequence. Here we review the research that led to the replication fork trap theory, and we aim to integrate several recent findings that contribute towards an understanding of the physiological roles of the replication fork trap. Likely roles include the prevention of over-replication, and the optimization of post-replicative mechanisms of chromosome segregation, such as that involving FtsK in Escherichia coli.